ISLAMOPHOBIA (Analisis Sosiologi Trust Terhadap Islam di Barat) - Syahrir Ibnu (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2013)
Islamophobia is a symptom of a doctrine that has existed in the Western societies. The justification for Islamophobia escalates following the great tragedy of the WTC bombing in New York on September 11 2001. Islamophobia is not a rootless issue but a scheme of trying to break the trust of the west against Islam. Islamophobia is an issue raised in the campaign for elections in the European countries and the United States to win votes. Islamic people should make efforts to fight against this issue by using the media to show the true peaceful Islamic life and should not make violence as the only choice to resolve clash of civilizations.Keywords: Islamohobia, Clash of Civilizations